Safety and efficacy of topical bacteriophage and ethylenediaminetetraacetic acid treatment of Staphylococcus aureus infection in a sheep model of sinusitis. Issue 3 (21st January 2014) - Drilling, Amanda; Morales, Sandra; Boase, Samuel; Jervis‐Bardy, Joshua; James, Craig; Jardeleza, Camille; Tan, Neil Cheng‐Wen; Cleland, Edward; Speck, Peter; Vreugde, Sarah; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Treatment of sinonasal bacterial biofilms continues to be a challenge in modern rhinology. This study's objective was to assess the safety and efficacy of topically applied Cocktail of S. aureus specific phage (CTSA) alone and in combination with ethylenediaminetetraacetic acid (EDTA) for treatment of Staphylococcus aureus biofilms in vivo. Methods Using a sheep model of sinusitis, frontal sinuses (n = 6 per treatment) were flushed once daily with a CTSA (2 × 106 plaque forming units [PFU]/mL), with or without EDTA (0.075 mg/mL), and compared to a control flush containing saline and heat‐inactivated CTSA. Safety was assessed using histology and scanning electron microscopy (SEM) after treatment for 3 days. Efficacy was assessed by quantifying the generation of S. aureus biofilms in the frontal sinuses after 5 days of treatment. Biofilm mass was compared between treatment groups and controls using LIVE/DEAD BacLight staining and confocal scanning laser microscopy to visualize the tissue sections. COMSTAT2 software was used to compute the biofilm mass present on tissue sections. Results Tissue morphology was conserved, with no significant signs of inflammation, when comparing control and test treatments. Furthermore, SEM analysis indicated test treatments were not toxic or damaging to mucosal cilia. COMSTAT2 quantification of biofilm showed a significant reduction in biofilm levels when comparing the control with CTSA (p = 0.0043), EDTA (p = 0.0095), and CTSA‐EDTA (p = 0.0022) treatments. Conclusion Results indicate that CTSA and EDTA are safe and efficacious for short‐term topical application against S. aureus infection in a sheep sinusitis model, and have the potential to be translated to a clinical setting.